The Organic Fertilizers Residuals and Earthworm Introduction on Growth and Yield of Upland Rice - Dick Dick Maulana; Suli Suswana (Agrotechnology Research Journal, 2018)
In modern agriculture, over use of inorganik fertilizers causes dangerous effects on environment, human health and loss of soil fertility. Soil organic matter is a main indicator of the quality and healthy soils. Organic matter mineralization is a key process that releasing the available nutrients to the plants. There are many organisms involved in the mineralization processes. Earthworm enable to digest soil organik matters, and the excretion’s have more available nutrients content, that potential to increase nutrients absorption. This research intended to study influences of organic fertilizers residuals and earthworm introduction on growth of the upland rice in pots. The experiment was conducted in Agricultural Faculty of Universitas Islam Nusantara (UNINUS), from January – June 2017, with RBD that comprised of two factors: (1) earthworm; and (2) residual of kinds and rates of the organik fertilizers. The results showed that aren’t significantly interaction influences of the organik fertilizers residuals and earthworm introduction on growth and yield of upland rice also to increase yield components of upland rice.